The Effect of Drill Training Method on Badminton Backhand Hit Skills at PB Club. Sarma Pangkalpinang - Ramadhan, Sahrul; Putranto, Dedy; Oktarina, Oktarina (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Lack of proficiency in badminton backhand shots was the driving force behind this study. Through analysis during the initial observation, the researcher found that there were still training patterns that had yet to be considered so that they were more reproduced in games. There was no variety of exercises applied. Therefore, researchers researched to determine the effect of the drill training method on badminton backhand shot skills. This type of research is quantitative research using the